2014
DOI: 10.1159/000358467
|View full text |Cite
|
Sign up to set email alerts
|

Preterm Nutrition and the Brain

Abstract: The brain is the most highly metabolic organ in the preterm neonate and consumes the greatest amount of nutrient resources for its function and growth. As preterm infants survive at greater rates, neurodevelopment has become the primary morbidity outcome of interest. While many factors influence neurodevelopmental outcomes in preterm infants, nutrition is of particular importance because the healthcare team has a great deal of control over its provision. Studies over the past 30 years have emphasized the negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 26 publications
1
68
0
1
Order By: Relevance
“…For As, Cd, Pb, Mn, and Hg, we hypothesized that higher levels of exposure would associate with more NR3C1 methylation and thus treated the low tertile group as the reference category in analysis. As some Zn exposure is necessary for healthy fetal brain development, 59,60 we hypothesized that low levels of Zn exposure would be associated with increased NR3C1 methylation. Thus, the high tertile group was the reference category for Zn analyses.…”
Section: Metals Exposurementioning
confidence: 99%
“…For As, Cd, Pb, Mn, and Hg, we hypothesized that higher levels of exposure would associate with more NR3C1 methylation and thus treated the low tertile group as the reference category in analysis. As some Zn exposure is necessary for healthy fetal brain development, 59,60 we hypothesized that low levels of Zn exposure would be associated with increased NR3C1 methylation. Thus, the high tertile group was the reference category for Zn analyses.…”
Section: Metals Exposurementioning
confidence: 99%
“…Instead, there are tangible aspects of the social and physical environments that actively work to promote health. For example, zinc is a naturally occurring element in the environment essential for healthy brain development [75] and has also been shown to mitigate the deleterious effects of cadmium exposure [76]. Likewise, recent work has shown that warm and empathetic parenting behaviors and safe and stable family lives can enhance development of favorable cardiovascular health [64,77].…”
Section: Conclusion and The Way Forwardmentioning
confidence: 99%
“…The reality is that many preterm infants fed even fortified human milk may demonstrate growth, meeting specified weight goals, but 43% are still documented as small for gestational age and are in the lower growth percentiles at discharge—unlike their term counterparts [18,19,20]. Most concerning is that growth failure—particularly linear velocity—is associated with neurodevelopmental morbidities [21,22,23]. In addition, a recent multi-site trial randomly assigning infants to donor milk or preterm formula did not find developmental advantages [24].…”
Section: Introductionmentioning
confidence: 99%